Understanding Antimicrobial Resistance from the Perspective of Public Policy: A Multinational Knowledge, Attitude, and Perception Survey to Determine Global Awareness - SoeYu Naing; Max van Wijk; Jordi Vila; Clara Ballesté-Delpierre (MDPI AG, 2021)
Minimizing the effect of antimicrobial resistance (AMR) requires an adequate policy response that relies on good governance and coordination. This study aims to have a better comprehension of how AMR is understood and perceived by policy-makers and stakeholders in a multinational context. A digital survey was designed to capture the knowledge, attitudes, and perceptions (KAP) towards AMR, and it was distributed to politicians, policy advisors, and stakeholders. A total of 351 individuals from 15 different countries participated, 80% from high-income countries (HICs) and 20% from low- and middle-income countries (LMICs). The Netherlands, Spain, and Myanmar were the top 3 represented countries. Participants had sufficient knowledge regarding AMR and reported the importance of political willingness to tackle AMR. Overall, LMIC participants demonstrated better knowledge of AMR but showed poor perception and attitude towards antimicrobial use compared to HIC participants. In addition, level of education and field of expertise were significantly associated with knowledge, perception, and practices regardless of demographic characteristics. Inter-regional differences in KAP regarding AMR exist among politicians, policy advisors, and relevant stakeholders. This study captures multinational policy-maker and stakeholder mapping that can be used to propose further policy implementation on various governance levels.